Pembentukan Daerah Otonomi Baru: Pemekaran Provinsi Kepulauan Nias - Zendrato, Ahmad Fahmi; Nursadi, Harsanto (Legal Spirit, 2024)
Indonesia adheres to the principle of decentralization in administering its government. Each region has the right and is given the authority to manage its own government affairs. The granting of broad autonomy to the regions is directed at accelerating the realization of social welfare through service improvement, community empowerment and participation. Law No. 23 of 2014 wants the birth of a new autonomous region in Indonesia. The implementation mechanism is further regulated in Government Regulation No. 78 of 2007. Expansion of regions is one of the efforts to accelerate national development. The conditions that must be met in the expansion of the new autonomous regions include: 1) basic territorial requirements; 2) regional capacity requirements; and 3) administrative requirements. The Nias Islands are an area that has been planned to be split into a new autonomous region. The research method used is empirical juridical, namely research conducted to analyze the implementation of legal norms that apply in society. Discussions regarding the plan for regional division of the Nias Islands have started since 2009 but until now there has been no realization from the central government. The obstacle to the expansion of the division is the existence of a moratorium set by the President. Regional expansion is also considered to be a burden on state finances considering that apart from the Nias Islands, there are still many other regions that have also proposed to do division. However, when an area meets the requirements for expansion as stipulated in Government Regulation No. 78 of 2007 and there is an urgency why the area must be divided immediately. It is better if the moratorium is lifted so that each region that has met the requirements to carry out expansion can become a new autonomous region and become more developed because it is given the authority to manage its own region.